Analysis of an E-Wallet ShopeePay Satisfaction Model - Nella Aginta Pinem; Mirza Mirza (Clean and Sustainable Production, 2023)
This study aims to analyze the effect of product quality, promotion, and brand image on purchasing decisions on Kenbike spare parts products. The research design uses quantitative research methods with a causal approach to determine the relationship between variables, both independent and dependent variables. The sampling technique in this study used a non- probability sampling technique. Respondents in this study were 100 calculated based on the Rao Purba formula using SPSS version 22. The sampling method used was purposive sampling. The data collection method used a survey method with research instruments through a questionnaire. The research results that have been obtained after testing the Hypothesis Test Model indicate that product quality has a positive and significant effect on purchasing decisions. Promotion has a positive and significant effect on purchasing decisions. brand image has a positive and significant effect on purchasing decisions.